2013
DOI: 10.1021/jf4003126
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenolic and Hydroxycinnamate Contents of Whole Coffee Fruits from China, India, and Mexico

Abstract: 1Air dried whole coffee fruits, beans and husks from China, India and Mexico were analysed 2 for their chlorogenic acids (CGA), caffeine, and polyphenolic content. Analysis was by 3 HPLC and Orbitrap exact mass spectrometry. Total phenol, total flavonol and antioxidant 4 capacity were measured. 5The hydroxycinnamate profile consisted of caffeoylquinic acids, feruloyquinic acids, 6 dicaffeoylquinic acids and caffeoyl-feruloylquinic acids. A range of flavan-3-ols as well as 7 flavonol conjugates were detected. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
69
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 67 publications
7
69
0
2
Order By: Relevance
“…Adults had a coffee consumption 25% higher than teenagers, approximately 25 . Coffee is known to possess large quantities of phenolic compounds, especially of the class of phenolic acids, being considered the major dietary source of hydroxycinnamic acids 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Adults had a coffee consumption 25% higher than teenagers, approximately 25 . Coffee is known to possess large quantities of phenolic compounds, especially of the class of phenolic acids, being considered the major dietary source of hydroxycinnamic acids 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the compound, such as chlorogenic acid and polyphenols, which contributed to the antioxidant activity in coffee, is geographically related [ 18 ]. The coffee fruit was found to have more chlorogenic acids (CGA) in Arabica coffee fruit planted in Mexico and India compared to the coffee fruit grew in China.…”
Section: Review Of Publications On Determination Of Coffee Antioximentioning
confidence: 99%
“…The previous study reported that coffee husk and coffee pulp had been used as non-food ingredients, such as for compost, bio absorbents, bioethanol production or caffeine extraction (GURRAM et al, 2016;MURTHY, NAIDU, 2012;SETYOBUDI, et al, 2018). Whereas coffee husk and coffee pulp have great potential as a functional food ingredient (SETYOBUDI et al, 2019) due to its components contained such as of proteins (8 % to 11 %), lipids (0.5 % to 3 %), minerals (3 % to 7 %), carbohydrates (58 % to 85 %), reducing sugars (14 %), caffeine (~1 %), and tannin (~5 %) and 0.2 mg g −1 to 1.9 mg g −1 of 5-O-caffeoylquinic acid compound, the main phenolic compound found in Arabica and Robusta coffee (FRANCA, OLIVEIRA, 2009;MULLEN et al, 2013). Some of the studies that have been conducted to utilize coffee husk as a dietary fiber ingredient (BENITEZ et al, 2019), a food supplement (ESQUIVEL, JIMÉNEZ, 2012;BLINOVÁ, L. et al, 2017); an antioxidant and anti-bacterial (MURTHY et al, 2012;DUANGJAI et al, 2016).…”
Section: Introductionmentioning
confidence: 99%